Genome-Wide Network of lncRNA–mRNA During Ovine Oocyte Development From Germinal Vesicle to Metaphase II in vitro - Wang, Jun-Jie; Niu, Meng-Han; Zhang, Teng; Shen, Wei; Cao, Hong-Guo (Frontiers in Physiology, 2020)
Long non-coding RNA (lncRNA) is involved in many biological processes and, owing to the prevalence of sequencing technology in animals, it has been closely investigated. However, similar research in ovine ovarian development is scant and poorly understood, particularly in relation to the molecular mechanisms of ovine oocyte maturation. In the current study, RNA sequencing was performed with germinal vesicle (GV) stage oocytes isolated from local Chinese ewes, and metaphase II (MII) stage oocytes derived from cumulus oocyte complexes (COCs) after maturation in vitro. Using bioinformatics analysis, abundant candidate lncRNAs in stage-specific ovine oocytes were identified and their trans- and cis-regulatory effects were deeply dissected using computational prediction software. Functional enrichment analysis of these lncRNAs revealed that they were involved in the regulation of many key signaling pathways during ovine oocyte development, which was reflected by their targeted genes. From this study, multiple lncRNA-mRNA networks were presumed to be involved in key signaling pathways regarding ovine oocyte maturation and meiotic resumption from GV to MII stages. In particular, one novel lncRNA (MSTRG.17927) appeared to mediate the regulation of PI3K signaling during ovine oocyte maturation. Therefore, this research offers novel insights into the molecular mechanisms underlying ovine oocyte meiotic maturation regulated by lncRNA-mRNA networks from a genome-wide perspective.